2018
DOI: 10.1080/01426397.2018.1518518
|View full text |Cite
|
Sign up to set email alerts
|

Children’s interactions with water in city centres: a case study from Sheffield, UK

Abstract: Children's experiences of outdoor environments have been studied now for more than forty years yet no research has specifically focussed on children's experiences of water play in constructed spaces of city centres. This paper discusses the development of an observational mapping tool, called TOWEC, to record the interaction of children with water. It then reports findings and analysis from 3,399 observations over a year long period of children interacting with water in the award winning public open space of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Another observation was that even if children passed by the wet pond, they did not interact with the water because it was either not detected or not attractive. We know that children's interactions with water features are influenced by different parameters such as age, weather, and localities (i.e., Bozkurt, Woolley, & Dempsey, 2019;Kytta, 2002). Yet, it also depends on the socio-cultural practices of authority figures (i.e., the norms and considerations that affect children's perception of affordances largely; Kytta, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Another observation was that even if children passed by the wet pond, they did not interact with the water because it was either not detected or not attractive. We know that children's interactions with water features are influenced by different parameters such as age, weather, and localities (i.e., Bozkurt, Woolley, & Dempsey, 2019;Kytta, 2002). Yet, it also depends on the socio-cultural practices of authority figures (i.e., the norms and considerations that affect children's perception of affordances largely; Kytta, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed (Bozkurt, Woolley and Dempsey, 2019) no existing tool was suitable for mapping and recording children in public open spaces. Most previous tools have been used to observe children in enclosed spaces, such as school playgrounds (Moore, 1989;; have meant that only a limited number of children could be observed (Moore, 1989; or have observed physical activity and not specifically play (McKenzie et.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…A new mechanism, called a Tool for Observing Water Experiences of Children (TOWEC) was designed for hand coding with symbols representing gender, age, and ethnicity. The tool also facilitated the hand recording of information including environmental characteristics; characteristics of children; and passive or active play with water as observations during the pilot study (Bozkurt, Woolley and Dempsey, 2019).…”
Section: Data Collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The informal interviews was a complementary method used to extend research and allow for deeper understanding of what was observed. A similar research method was used by Kyttä (2002), Bozkurt et al (2018) or Chaudhury et al (2019). In the sections "Discussion" and "Conclusion" a modification of the taxonomy in comparison with the original table and the alternatives of other authors is evaluated.…”
Section: Introductionmentioning
confidence: 99%